Properties of the averaging along the characteristics hyperbolic of the system operator - Krylovas, Aleksandras; Lavcel-Budko, Olga (Lietuvos matematikos rinkinys, 2012)
Examing the averaged equations system with periodic initial conditions. Proved the lemmas, which allow to reorganize the system in to the form similar to a semi-linear hyperbolic system written in Riemann invariants. This allows to set conditions for the existence of the solution.
Keywords: asymptotical methods; averaging; nonlinearwaves; hyperbolic system